The iron Silk Road: how important is it?. Issue 2 (2nd April 2020) - Bucsky, Péter
ABSTRACT: Container transport by railway between Europe and China is a flagship project of China's Belt and Road Initiative (BRI). Trade, economic and geopolitical aspects of the BRI have been widely analysed, but data on real traffic flows are scarce. A variety of data sources are examined to identify the structure and evolution of cargo volumes along the Eurasian Land Bridge in the light not just of the development of new railway freight services between Chinese cities and Europe but also of trade between Japan and South Korea and European countries. The roles of subsidies and new infrastructure investments in shaping past, present and futures trends are also examined.